Peptide vaccines: an innovative therapeutic approach against antibiotic-resistant bacterial infections - Tavassoli Razavi, Fatemeh; Salari, Nasrin; Emami, Atena; Haghmorad, Dariush; Baharlou, Rasoul (Frontiers in Immunology, 2025)
Bacterial infections continue to pose a serious threat to global health, especially with the growing challenge of multidrug-resistant pathogens. While traditional vaccines have been pivotal in reducing disease burden, they come with limitations such as variable efficacy, safety concerns, and limited ability to address the diversity of bacterial strains. This review highlights the promise of peptide-based vaccines as an innovative approach to overcoming these hurdles. By targeting specific regions of bacterial proteins, peptide vaccines can elicit precise immune responses with improved safety and broader applicability. Advances in technology, including bioinformatics and delivery systems, have enhanced their design, making them more stable, effective, and easier to produce. These vaccines work by activating both antibody and T-cell responses through well-defined mechanisms. Different types, such as linear peptides, cyclic peptides, and synthetic long peptides, offer diverse strategies to tailor immune protection. The role of adjuvants and advanced delivery methods, like nanoparticles and liposomes, further improve their potential. Exciting progress has been made against the ESKAPE pathogens — Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter spp. Peptide vaccines offer a forward-thinking, adaptable solution to reduce bacterial infections and mitigate the rise of antibiotic resistance, paving the way for safer and more effective prevention strategies. This review underscores the critical role of peptide-based vaccines in combating bacterial infections, advocating for ongoing research to unlock their full potential.